Genetic differentiation among Batak fish populations (Neolissochilus sumatranus, Tor douronensis, and Tor soro) in North Sumatra, Indonesia revealed by RAPD markers - TERNALA ALEXANDER BARUS; HESTI WAHYUNINGSIH; BERTUA NOVITA SIMANJUNTAK; RISSA HERAWATI GINTING; AGUNG SETIA BATUBARA; ADRIAN HARTANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Barus TA, Wahyuningsih H, Simanjuntak BN, Ginting RH, Batubara AS, Hartanto A. 2023. Genetic differentiation among Batak fish populations (Neolissochilus sumatranus, Tor douronensis, and Tor soro) in North Sumatra, Indonesia was revealed by RAPD markers. Biodiversitas 24: 1327-1332. Mahseer or Batak fish species within the genera of Neolissochilus and Tor are highly valued as a source of food for local communities, especially in North Sumatra. Assessment of genetic differentiation of the Batak fish population, namely Tor soro, Tor douronensis, and Neolissochilus sumatranus in the North Sumatra Rivers, has been conducted. The objective of this study was to determine the possible genetic divergence among congeneric fish and supply the genetic information for the design of conservation strategies. Fish specimens were collected from three rivers in North Sumatra Bahorok River (Langkat District), Asahan River (Toba Samosir District), and Batangtoru River (South Tapanuli District). The genetic analysis employed the Random Amplified Polymorphism DNA (RAPD) markers using a set of RAPD primers: OPA-2, OPA-3, OPA-6, OPA-7, OPA-9, OPA-11, and OPA-17. The amplified fragments were analyzed using the Numerical Taxonomy and Multivariate Analysis System (NTSYS) 2.00 program to construct the dendrogram of relationship among accessions. The genetic similarity coefficient among species of T. soro, T. douronensis, and N. sumatranus reached 0.44-0.86, with the lowest similarity at 44%. The cluster analysis indicated that T. douronensis is more closely related to N. sumatranus than T. soro based on the grouping of accessions. There is an indication of natural hybrids occurrence between N. sumatranus and T. soro populations despite the different habitats and locations of sampling. Our study revealed that using RAPD markers may discriminate inter- and intraspecific Batak fish populations in North Sumatra.